Fluorine Substituted Bithiophene Imide‐Based n‐Type Polymer Semiconductor for High‐Performance Organic Thin‐Film Transistors and All‐Polymer Solar Cells (Solar RRL 2∕2019). Issue 2 (11th February 2019) - Sun, Huiliang; Tang, Yumin; Guo, Han; Uddin, Mohammad Afsar; Ling, Shaohua; Wang, Ruizhi; Wang, Yingfeng; Zhou, Xin; Woo, Han Young; Guo, Xugang
Abstract : In article no.1800265, Xugang Guo and co‐workers introduce F atoms to the Β‐position of bithiophene imide, generating a novel electron‐deficient building block s‐FBTI2, a well desired "stronger acceptor" for n‐type polymer semiconductors. The resulting semiconductor shows remarkable electron mobility, approaching 3.0 cm 2 V −1 s −1 in organic thin‐film transistors, and a promising power conversion efficiency of 6.50% in all‐polymer solar cells.